Extracting OPE coefficient of Konishi at four loops - Goncalves, Vasco [UNESP] (Springer Nature, 2017)
In this short note we compute the OPE coefficient of two 20′ operators and the Konishi operator. To this end, we use the OPE decomposition of a four point function of four 20′ operators and the method of asymptotic expansions to compute the leading term, in the OPE limit, of all integrals contributing to the four point function.
Keywords: AdS-CFT Correspondence; Conformal Field Theory